2017
DOI: 10.1186/s12889-017-4480-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the intergenerational persistence of health behaviour: an empirical study of smoking from China

Abstract: BackgroundIt is of significance to look into the intergenerational transmission of risk behaviour to explain the disparity of health. Our paper contributes to the literature by providing evidence in the context of China, focusing on smoking behaviour.MethodsThis paper studies the intergenerational transmission of smoking in the context of China using a nationally representative dataset – the China Health and Nutrition Survey (CHNS). The two-part model, the Tobit model, and the fixed effects model are utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
1
14
2
Order By: Relevance
“…There were also differences between paternal in uence and maternal in uence. We found father's smoking behavior had a greater signi cant effect on leading children's smoking behavior than the mother's, contrary to many previous studies [14,15,18,19]. This may be because, compared with previous studies, the sample size of maternal smoking in this study was too small to make good statistical inferences.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…There were also differences between paternal in uence and maternal in uence. We found father's smoking behavior had a greater signi cant effect on leading children's smoking behavior than the mother's, contrary to many previous studies [14,15,18,19]. This may be because, compared with previous studies, the sample size of maternal smoking in this study was too small to make good statistical inferences.…”
Section: Discussioncontrasting
confidence: 95%
“…The present study showed that consistent with many previous ndings [14-19, 21, 23-25], parental risky health behaviors could be signi cantly transmitted to their children. Children are usually easy to imitate their parents' behavior, even if it is negative and unhealthy [14,29,30]. So, parents' words and deeds are very important to prevent children's risky health behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are number of studies regarding the effects of tobacco on those countries. Jay found a co-relationship between parent's smoking and child smoking in China (Jay, 2017). Ikeda clarified that tobacco smoking and high blood pressure were two major risk factors for adult mortality in Japan (Ikeda, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Next, as focus groups were held with multiple individuals, social desirability biases may have influenced the participants' responses. Although data were captured from 2013-2014, this study's findings are likely still applicable to the target population in 2020, as health and smoking behaviours, which are influenced by culturally rooted factors, have been found to be intergenerationally persistent among Chinese smokers 15,40 . Additionally, more recent studies have identified similar culturally ingrained beliefs about smoking practice and cessation among Chinese-Canadian immigrant groups 16,21 , as well as other Chinese immigrant groups 17,41 .…”
Section: Strengths and Limitationsmentioning
confidence: 98%